Two Unique Cases of X-linked SCID: A Diagnostic Challenge in the Era of Newborn Screening - Purswani, Pooja; Meehan, Cristina Adelia; Kuehn, Hye Sun; Chang, Yenhui; Dasso, Joseph F.; Meyer, Anna K.; Ujhazi, Boglarka; Csomos, Krisztian; Lindsay, David; Alberdi, Taylor; Joychan, Sonia; Trotter, Jessica; et al. (Frontiers in Pediatrics, 2019)
In the era of newborn screening (NBS) for severe combined immunodeficiency (SCID) and the possibility of gene therapy (GT), it is important to link SCID phenotype to the underlying genetic disease. In western countries, X-linked interleukin 2 receptor gamma chain (IL2RG) and adenosine deaminase (ADA) deficiency SCID are two of the most common types of SCID and can be treated by GT. As a challenge, both IL2RG and ADA genes are highly polymorphic and a gene–based diagnosis may be difficult if the variant is of unknown significance or if it is located in non-coding areas of the genes that are not routinely evaluated with exon-based genetic testing (e.g., introns, promoters, and the 5′and 3′ untranslated regions). Therefore, it is important to extend evaluation to non-coding areas of a SCID gene if the exon-based sequencing is inconclusive and there is strong suspicion that a variant in that gene is the cause for disease. Functional studies are often required in these cases to confirm a pathogenic variant. We present here two unique examples of X-linked SCID with variable immune phenotypes, where IL2R gamma chain expression was detected and no pathogenic variant was identified on initial genetic testing. Pathogenic IL2RG variants were subsequently confirmed by functional assay of gamma chain signaling and maternal X-inactivation studies. We propose that such tests can facilitate confirmation of suspected cases of X-linked SCID in newborns when initial genetic testing is inconclusive. Early identification of pathogenic IL2RG variants is especially important to ensure eligibility for gene therapy.